Polymorphism of S19W of apolipoprotein A5gene in patients with type 2 diabetes mellitus - connection with metabolic parameters and triglyceride levels - S. A. Skoryukova; M. V. Kim; A. A. Bystrova; A. Yu. Babenko; E. I. Baranova; S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2015)
The article deals with genetic aspects of the influence of S19W polymorphic variants of apolipoprotein A5 gene, on the blood lipids in patients with type 2 diabetes mellitus, as well as influence of various clinical and anamnestic parameters on the blood lipids determining the development f atherogenic dyslipidemia.. The study revealed interrelation between 19W allele and hypertriglyceridemia development in patients with type 2 diabetes mellitus.